The Design of Emotionally Resonant Learning Experiences: Prospect-Refuge, Framing, and Friction - Sniderman, Sarah (International Journal of Advanced Corporate Learning (iJAC), 2025)
As learning professionals, we often neglect the emotional aspects of the learning process, especially for adults and even more particularly in the context of corporate learning and performance. Anxiety, uncertainty, and vulnerability can become stumbling blocks as learners work through the transition from who they are to who they are in the process of becoming. The principles of prospect-refuge, framing, and friction – applied in fields such as architecture, urban design, and visual art – can provide powerful insight into the design of meaningful, supportive, and emotionally resonant learning experiences.